Syntactic Figures in Nazar Eshonqul’s Prose and Their Stylistic Function: A Comprehensive Analysis (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study provides a comprehensive analysis of syntactic figures in Nazar Eshonqul’s prose, highlighting their significance in shaping narrative structure and thematic depth. Through a close examination of Tobut, Xayol Tuzog‘i, and Shamolni Tutib Bo‘lmaydi, the research identifies parallelism, repetition, inversion, ellipsis, and metaphor as key elements of his distinctive style. Far from serving as mere embellishments, these devices function as integral structural and philosophical tools, probing themes of existential uncertainty, cultural memory, and identity. By blending Sufi poetic traditions with modernist experimentation, N.Eshonqul constructs a fragmented syntax that reflects the complexities of contemporary Uzbek consciousness.